2012
DOI: 10.1108/17561451211273374
|View full text |Cite
|
Sign up to set email alerts
|

Health and safety: teaching law, educating for prevention

Abstract: The teaching of law to non-lawyers can involve an unreceptive audience, particularly when the subject is health and safety. The author works with prospective rural practice chartered surveyors who are likely to be professionally involved with the two highest risk working environments in the UK : construction 1 and agriculture. 2 Unlike construction, the agricultural industry has failed to reduce annual fatalities in the past quarter of a century and continues to account for around 20% of workplace deaths, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…These are the constructs required by the organization in its safety policies and strategy issues to minimize the prevalence of OHS. Similar studies showed that strategy issues in an organization motivate managers to formulate safety guidelines and procedures (De Silva, 2012;De Silva et al, 2018;EY and Y, 2015;Iavicoli et al, 2011;KUO et al, 2009;Machfudiyanto et al, 2017;Milgate et al, 2002;Tang et al, 2011).…”
Section: Measurement Of Constructsmentioning
confidence: 93%
“…These are the constructs required by the organization in its safety policies and strategy issues to minimize the prevalence of OHS. Similar studies showed that strategy issues in an organization motivate managers to formulate safety guidelines and procedures (De Silva, 2012;De Silva et al, 2018;EY and Y, 2015;Iavicoli et al, 2011;KUO et al, 2009;Machfudiyanto et al, 2017;Milgate et al, 2002;Tang et al, 2011).…”
Section: Measurement Of Constructsmentioning
confidence: 93%
“…Having explored using case law as a base in the past (de Silva, 2012) this paper considers the use of a form of the Socratic method with the intention of engaging student interest, enhancing legal skills and engendering an understanding of the importance of both the law and the transferability of legal studies and skills.…”
Section: Why Be Concerned With Teaching Method?mentioning
confidence: 99%
“…This paper develops previous work on issues raised when teaching law to, in particular, non-law students (de Silva, 2012;2013;. Having decided to trial a more structured variation of the usual student questioning which would take place in tutorials, a consideration of the development, use and purpose of the Socratic method has been conducted in order that a deeper understanding of the method's origins and varied usage informs the form of implementation and most beneficial use with current property students.…”
Section: Introductionmentioning
confidence: 99%
“…Developing and improving the quality of teachinglearning requires explaining the current situation and identifying the challenges and problems and its strengths (Ahmady & Khani, 2022). The "law school" approach, as is therefore clearly evident, in particular: the students will engage in a high volume of reading; where, a wide range of topics must be covered in limited detail, and where nature of the subject has, a very practical aspect (De Silva, 2012).…”
Section: Teaching Civil Procedures II To Final Year Studentsmentioning
confidence: 99%